If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + 1) = 189 Reorder the terms: X + (1 + x) = 189 Remove parenthesis around (1 + x) X + 1 + x = 189 Reorder the terms: 1 + X + x = 189 Solving 1 + X + x = 189 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + X + -1 + x = 189 + -1 Reorder the terms: 1 + -1 + X + x = 189 + -1 Combine like terms: 1 + -1 = 0 0 + X + x = 189 + -1 X + x = 189 + -1 Combine like terms: 189 + -1 = 188 X + x = 188 Add '-1x' to each side of the equation. X + x + -1x = 188 + -1x Combine like terms: x + -1x = 0 X + 0 = 188 + -1x X = 188 + -1x Simplifying X = 188 + -1x
| 2x+3(5-4x)=15-10x | | 7n+k-8k-8n+3m= | | 8+2w=18 | | 5(x+9)+x=3(x+2)-8 | | -3x+3(x+16)=48 | | 0.22m+7.20=0.1m+8.40 | | 2w+3=7 | | 8(u+6)=24 | | 3(m-23)+3(m-2)=21 | | y=abs(2x) | | 6(2x-1)-10=2(5x-1) | | 8w+8-5w=5w-8 | | 2c-6d-13c+11e= | | 3m-9=-27 | | -w^2+2w=40 | | Rn+4f=9vforn | | 4x+8=24-12 | | 2x-4=4x-6-2x | | 217=77-u | | 4x+6+4x+4x+5=4x+4x+5x+5 | | 2(x-24)+4(x-3)=36 | | 2x+13=91 | | 7=3p-8 | | 19-13p=-17p-8 | | -35=-7+-6a | | 9v+2v-14v+8q= | | 9+5v=2v-9 | | 0=x^2-64x-512 | | 5+-(8)n=29 | | 21+2n=43 | | -164=-5-3(7m+4) | | cos(x)-cos(7x)=sen(4x) |